Ketamine and Norketamine: Enantioseparation, Enantioselective Ecotoxicity and Biodegradation Studies - Pereira, Ariana Isabel Perez (2020)
Ketamine (K), commercialized as a racemate, is used in pediatric and veterinary medicine as an anesthetic. However, it has been abusively used by adolescents and young adults in recreational environments due to its hallucinogenic and sedative effects. K and its main metabolite, norketamine (NK), have been detected either in effluents of wastewater treatment plants (WWTP) and in aquatic environments. Nonetheless, enantioselective biodegradation studies of K as well as ecotoxicity of K and NK in diverse aquatic organisms is still unknown. This work describes the development and validation of an enantioselective liquid chromatography to quantify the enantiomers of K and NK. The enantiomers were separated using an analytical Lux® 3 µm cellulose-4 column (150 × 4.6 mm internal diameter (I.D)) under isocratic elution mode. Optimized conditions consisted of ammonium acetate in ultra-pure water (with 0.1% of diethylamine (DEA)) and acetonitrile (70:30 v/v) as mobile phase at a flow-rate of 1 mL/min. The method was validated and demonstrated to be precise and accurate with a linearity range of 5 to 50 µg/mL for K and 2.5 to 25 µg/mL for NK. The limit of quantification was 1.25 µg/mL for NK enantiomers and 2.5 µg/mL for K enantiomers. The validated method was employed to follow a 21 days enantioselective biodegradation assay of K by activated sludge (AS). Results showed that K is poorly biodegraded which corroborates to its persistence in the aquatic environment. Also, enantioselectivity biodegradation was not observed and transformation products were not detected. In order to obtain the pure enantiomers of K and NK for the enantioselective ecotoxicological assays, a semi-preparative enantioseparation method was developed and optimized. The enantioseparation were achieved with an amylose 3,5-dimethylphenylcarbamate column coated on to APS-Nucleosil (500 A°, 7 µm, 20 %, w/w; 20 x 0.7 cm (I.D.)). Optimized conditions allowed recovery of enantiomers higher than 70%. The enantiomeric purity of the enantiomers was assessed by the analytical method and was close to 100%, except for K2 (≈ 97%). Acute and chronic toxicity assays were performed in two ecological relevant aquatic organisms at different concentrations, including concentrations at environmental level, for racemates and the pure enantiomers of K and NK. The ecotoxicity assays were performed using the crustacean Daphnia magna and the protozoan Tetrahymena thermophila in accordance with national and international standards (ISO and OECD). NK racemate presented higher mortality for crustacean D. magna compared to K. For both compounds mortality increased across gradient of exposure. Considering T. thermophila, K demonstrated greater growth inhibition compared to NK. These results demonstrate a species-dependent toxicity. Also, different enantioselective response between enantiomers of K and NK were found at the selected concentrations.